Neospora caninum infection dynamics in dairy cattle - Piagentini, Marcelo [UNESP]; Moya-Araujo, Carla Fredrichsen; Prestes, Nereu Carlos [UNESP]; Sartor, Izidoro Francisco (Springer, 2012)
Neospora caninum is considered in many countries as one of the key abortion agents in cattle. This study aims to investigate the parasite behavior in dairy cattle in the municipality of Avar,, SP, Brazil, where abortions frequently occur. An ELISA was performed to compare two samplings on a total of 615 animals; tests were performed in the same herds with a gap of 3 years. An increase in the percentage of reactive animals was observed, ranging from 21.6% at the first sampling to 38.9% at the second sampling. of the 176 animals tested at both samplings, 61.93% retained a non-reactive status, 15.9% retained a reactive status, 19.88% switched from non-reactive to reactive and 2.27% switched from reactive to non-reactive. of the 100 animals with reproductive disturbances, 50% presented anti-Neospora antibodies, thereby indicating the presence of the protozoa. When comparing cows and their respective female offspring, a predominance of horizontal infection was observed. Moreover, considering the significant percentage of animals that switched from non-reactive to reactive and the abundant presence of dogs among the herds, the N. caninum transmission may be attributed to presence of carnivores.